IMPROVING FOOD SAFETY MECHANISMS IN UZBEKISTAN (World Economics and Finance Bulletin, 2022)
This article is devoted to the issues of food safety, which is one of today's global economic problems, and the improvement of food safety mechanisms in Uzbekistan. In addition, the article reveals the extent of work carried out to ensure food safety in Uzbekistan on the basis of practical analysis, and relevant conclusions and recommendations are highlighted
Keywords: Milk and milk products; food products; food safety; food industry